Pró-letramento: um estudo sobre a resolução de problemas e as atitudes em relação à matemática apresentadas por professores do primeiro ciclo do ensino fundamental - Sander, Giovana Pereira [UNESP] (2014)
The present study aimed to investigate the possible changes in attitudes toward mathematics after the realization of the continued education course called Pró-Letramento, and investigate how these atitudes influence the practice of teaching mathematics through problem solving. 458 teachers participated of this study who teach in the early years of Elementary Public School system of cities in the state of São Paulo. The instruments used were: 1) a questionnaire, 2) a range of atitudes towards mathematics, 3) monitoring and recording of classes 4 participant teachers. The average calculated by the attitude scale was 63.15, which characterized 56.11% of teachers with a tendency to negative attitudes towards mathematics and 43.89% to positive attitudes. With regards to the Pró-Letramento course, the participant teachers stressed on contributions regarding the methodology of teaching mathematics, the use of concrete materials and the understanding of the contents. It was observed that working with problem solving was not very present in their speech. Regarding working with problem-solving activities, analysis of data showed that teachers with more positive attitudes toward mathematics work more frequently with the methods of problem-solving at various times during teaching, as before, during and after the teaching of a particular content that than the teachers with negative attitudes. The analysis of the monitoring of lessons the teachers showed different aspects related to problem-solving activities: the teacher with the most positive attitudes towards mathematics worked different types of problem situation, such as problems of daily life, standard issues and problem of logic; allowed the students to draw up the statement of the situation, and still seek resolutions for different situations. The teacher with the least positive attitudes... (Complete abstract electronic acess below)